1.1: Invited Paper: High Mobility Self‐Aligned Coplanar and BCE IGTO Semiconductor TFTs for Future Applications. (24th February 2021) - Seo, Hyun-Sik; Wu, Weihua; Li, GongTan; Xiao, Jun Cheng; Wu, Yuan-Chun; Zhao, Bin; ZHANG, Xin; Yan, Xiaolin
Abstract : Self‐aligned coplanar structure and back channel etched (BCE) structure have been developed using InGaSnO (IGTO) active layer. The mobility of IGTO TFT is around 25 cm 2 V −1 s −1 for both TFT structures. The 31 inch 4K2K (144ppi) top emission IJP AMOLED driven by self‐aligned coplanar IGTO TFTs and 10.7 inch 120 × 120 (× RGB) mini‐LED display driven by BCE IGTO TFTs are fabricated to verify IGTO TFT's characteristics. High mobility IGTO TFTs have been developed for future applications such as high resolution and narrow bezel OLED displays and micro‐LED displays.